Asuhan Kebidanan Pada Bayi Baru Lahir Di PMB Nurwati Wilayah Kerja UPTD Puskesmas Air Tiris - Susanti , Herlinda; Nislawaty, Nislawaty (Evidence Midwifery Journal, 2023)
Newborns can be interpreted as the period of life of the first baby outside the womb until the age of 28 days where there is a very big change from life in the womb to outside the womb. Providing Midwifery Care by using a midwifery management approach to the newborn Mrs. D at PMB Nurwati, Air Tiris Health Center Work Area in 2022. This writing uses a descriptive observational design in the form of a case study aimed at learning about midwifery care. This research is an assessment and collection of basic data which is the initial stage of midwifery management which is carried out using SOAP with a Varney mindset, namely subjective data assessment, objective data assessment, analysis and management according to the problems that By.Ny.D complained of, namely normal newborns. Based on the care given to By.Ny.D it has been done for 8 days. Based on the monitoring that was given for 8 days, the care provided to By.Ny.D had been running smoothly and there was an increase in the baby’s weight and the care provided had been running comprehensively